Prevalence of subclinical mastitis, related risk factors, and antimicrobial susceptibility of bacteria isolated from the milk of dairy cows in Kosovo - N Mazreku; D Sylejmani; A Robaj (Veterinární Medicína)
The purpose of this study was to determine the prevalence and risk factors associated with subclinical mastitis, as well as the antimicrobial susceptibility of bacteria isolated from the milk of dairy cows in the Republic of Kosovo. The study involved 242 lactating cows from 16 farms. Data were collected through questionnaire interviews, the California mastitis test (CMT), and microbiological analysis. For the detection and identification of bacteria, conventional methods and biochemical tests were used. The disc diffusion method was used to test the susceptibility of isolated bacteria. The prevalence of subclinical mastitis (SCM) at quarter and cow level was 22.3% and 10.5%, respectively. Factors including breed, age, parity, milk production, and lactation stage were significantly correlated with the occurrence of subclinical mastitis in cows (P < 0.05). Major bacterial isolates were Staphylococcus aureus (34%), coagulase-negative staphylococci (CNS, 21.3%), Escherichia coli (18.1%), Streptococcus uberis (14.9%), and Streptococcus agalactiae (4.3%). All bacterial isolates showed high susceptibility to gentamicin, tetracycline, amoxicillin/clavulanic acid, and sulfamethoxazole/trimethoprim and low susceptibility to penicillin and streptomycin.